Describing the Level of Awareness of Micro-Enterprises in Local Taxation - Rivera, Paul Cezam; Mirrar, Allene Kyle; Malazarte, Mark Nicole (TIJAB (The International Journal of Applied Business), 2024)
Background: Local taxes play a vital role in contributing significant socio-economic development and welfare in the city. This paper describes the level of awareness of micro-enterprises in local taxation. Objective: This study wants to comprehensively describe and conduct a detailed analysis of the level of awareness among micro-enterprises regarding local taxation in Pagadian City, how such awareness helped these owners manage their business operations, and where they stay informed about local tax ordinances. Method: This research employed a mixed-methods sequential explanatory design using a survey questionnaire. Then, the weighted mean and standard deviation, with the help of SPSS, were used to analyze the quantitative part of the research. It drew inspiration from Sharan Merriam's work, which emphasized the importance of patterns and themes. Results: This study revealed that micro-enterprise owners exhibit a high level of awareness regarding business taxes but need more awareness of amusement taxes. Awareness helped the owners in their business operations in the following ways: avoid penalties, smooth business operation, good decision-making, proper management, improvement skills, lessening tax stress, good reputation, successful business, business improvements, understanding customers, and properly registered. Additionally, the Bureau of Internal Revenue (BIR) emerged as the predominant source of knowledge concerning local tax ordinances. Conclusion: In Pagadian City, most micro-business owners understand local taxes. They know about Business Tax, which applies to all businesses, regardless of size. However, they must learn about amusement taxes due to the complex Philippine tax system.   Keywords: local tax ordinances, tax awareness, Philippine taxation, micro-enterprises, taxation